IMPLEMENTASI TANGGUNG JAWAB PEMERINTAH TERHADAP PEMELIHARAAN JALAN DI KABUPATEN BENGKALIS - Ruben, Awi; Asnawi, Eddy; Oktapani, Silm (Collegium Studiosum Journal, 2024)
Strategic district roads are roads that are prioritized to serve the interests of the district based on considerations to stimulate economic growth, welfare and security of the district, while city roads are roads located within the autonomous city area as referred to in the law on regional government. see the explanation of Article 9 (4) of Law Number 38 of 2004 concerning Roads. The purpose of this study is to analyze the implementation of government responsibility for road maintenance in Bengkalis Regency based on Law Number 38 of 2004 concerning Roads, to find obstacles and efforts to overcome obstacles in the implementation of government responsibility for road maintenance in Bengkalis Regency based on Law Number 38 of 2004 concerning Roads. The method used is sociological legal research. Based on the research results, it is known that the Implementation of Government Responsibility for Road Maintenance in Bengkalis Regency Based on Law Number 38 of 2004 concerning Roads has not run as it should, because in Bengkalis Regency there are still several damaged roads, this is certainly contrary to Law Number 38 of 2004 concerning Roads, which is a crucial aspect in ensuring connectivity and transportation security for the community.